Synthesis and Rietveld refinements of new ceramics Sr2CaFe2WO9 and Sr2PbFe2TeO9 perovskites. Issue 2 (15th March 2018) - El Hachmi, Abdelhadi; Tamraoui, Y.; Manoun, Bouchaib; Haloui, R.; Elaamrani, M.A.; Saadoune, I.; Bih, L.; Lazor, P.
Abstract : Ceramics of Sr2 CaFe2 WO9 and Sr2 PbFe2 TeO9 double perovskites have been prepared in polycrystalline form by solid-state technique, in the air. The crystalline structure was analyzed using X-ray powder diffraction (XRPD) at room temperature. Rietveld analysis of XRPD patterns show that both compounds adopt a tetragonal structure with space group I 4/ m, with unit cell parameters a = 5.5453(1) Å, c = 7.8389(1) Å for Sr2 CaFe2 WO9, and a = 5.5994(15) Å, c = 7.8979(30) Å for Sr2 PbFe2 TeO9 . A certain degree of anti-site disordering of W and/or Te and Fe on the B –sites have been detected, indicating the presence of a partial amount of W and/or Te at Fe positions and vice versa.